2006
DOI: 10.1016/j.cub.2005.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Cargo Regulates the Turnover of COPII Subunits at Single ER Exit Sites

Abstract: The COPII coat complex mediates the formation of transport carriers at specialized sites of the endoplasmic reticulum (ERES). It consists of the Sar1p GTPase and the Sec23/24p and the Sec13/31p subcomplexes . Both stimulate the GTPase activity of Sar1p , which itself triggers coat disassembly. This built-in GAP activity makes the COPII complex in principle unstable and raises the question of how sufficient stability required for cargo capture and carrier formation is achieved. To address this, we analyzed COPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
125
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 22 publications
23
125
0
Order By: Relevance
“…Sec23 overexpression might affect secretion due to its GTPase-activating protein activity (Yoshihisa et al, 1993;Antonny et al, 2001), whereas, although Sec13 labels cytosolic structures in BrightYellow 2 cells in the absence of Golgi cargo, these loci have not yet been equated unequivocally with ERES (Yang et al, 2005). We therefore chose to use Sec24, which is an established ERES marker in plants and other systems (Stephens et al, 2000;Forster et al, 2006;Matheson et al, 2006;Stefano et al, 2006). Moreover, we have demonstrated that Sec24 overexpression does not affect ER export (Fig.…”
Section: Eres Biogenesis Is Cargo Inducedmentioning
confidence: 98%
“…Sec23 overexpression might affect secretion due to its GTPase-activating protein activity (Yoshihisa et al, 1993;Antonny et al, 2001), whereas, although Sec13 labels cytosolic structures in BrightYellow 2 cells in the absence of Golgi cargo, these loci have not yet been equated unequivocally with ERES (Yang et al, 2005). We therefore chose to use Sec24, which is an established ERES marker in plants and other systems (Stephens et al, 2000;Forster et al, 2006;Matheson et al, 2006;Stefano et al, 2006). Moreover, we have demonstrated that Sec24 overexpression does not affect ER export (Fig.…”
Section: Eres Biogenesis Is Cargo Inducedmentioning
confidence: 98%
“…a Golgi-resident glycosylation enzyme, may experience a negative mismatch in the ER after having passed the quality control machinery. It will hence form clusters that can modulate the local turnover rate of COPII proteins [20] to facilitate the formation of a COPII vesicle. Having pinched off, the vesicle eventually arrives at the Golgi apparatus and fuses with the cis-most cisterna.…”
Section: Model For Hydrophobic Mismatch-driven Protein Sorting Betweementioning
confidence: 99%
“…For COPII, FRAP experiments show that the coatomer exchange rate between the ER membrane and the cytosol is doubled in the absence of cargo. This has been attributed to the increase of k off with decreasing cargo density (15).…”
Section: Discussionmentioning
confidence: 98%
“…It occurs at a rate k off , assumed constant here for simplicity [see supporting information (SI) Appendix for a discussion of this assumption]. This rate can be estimated from FRAP experiments (10,12,14,15), k off ≈ 0.1 − 10 s −1 . Under the assumption of constant protein density in the coat, the dissociation of monomer from the coat is followed by a rapid rearrangement of the coat structure and by a slight shrinkage of the coat; monomer inactivation thus opposes coat expansion.…”
Section: Description Of the Modelmentioning
confidence: 99%